Perilaku Prososial Dalam Persfektif Islam - Harmalis Harmalis (Departement of Mathematics Education, 2023)
Prosocial behavior is a form of behavior that plays an important role in coloring the relationship between one individual with another individual. Relationships between individuals will be more fun and comfortable when one of the individuals performs prosocial behavior. Individuals who like to do prosocial behavior will be more liked and liked by many people and vice versa, individuals who are reluctant to do prosocial behavior or not to go to prosocial in interacting with others will be shunned and disliked. Thus it can be understood that prosocial behavior is a very useful in maintaining and improving harmonious relationships between human beings. In Islamic perspective Prosocial behavior is a highly recommended thing, because individuals who do prosocial behavior will get rewards from Allah SWT in the form of rewards and practices for them and so do individuals who get help will feel happy and pleasant so that it can create and foster relationships warmer and more fun. The growth and increase in prosocial peril for adherents of Islam can be done by means of a medoration, and follow all commands and stay away from all prohibitions in the Qur'an and Hadith. The purpose of writing is to describe the importance of prosocial behavior in interclation between human beings and matters relating to Islamic views on prosocial behavior. The method in this writing is a literature study, namely by describing and analyzing some of the theories of psychology and Islamic views about prosocial peril.